Protective Effects of Dioscin Against Doxorubicin-Induced Hepatotoxicity Via Regulation of Sirt1/FOXO1/NF-κb Signal - Song, Shasha; Chu, Liang; Liang, Huifang; Chen, Jin; Liang, Junnan; Huang, Zhao; Zhang, Bixiang; Chen, Xiaoping (Frontiers in Pharmacology, 2019)
Doxorubicin (DOX), an antitumor antibiotic, has therapeutic effects on many kinds of tumors. However, DOX can produce some seriously side effects, which limit its clinical application. Thus, exploration of effective drug targets or active lead compounds against DOX-induced organ damage is necessary. Dioscin, one natural product, has potent effects against DOX-induced renal injury and cardiotoxicity. However, the effects of dioscin on DOX-induced hepatotoxicity have not been reported. In this study, the results showed that dioscin significantly ameliorated DOX-induced cell injury, reduced ROS level and suppressed cell apoptosis in αmouse liver 12 (AML12) cells caused by DOX. In vivo, dioscin evidently decreased the levels of ALT, AST, MDA, increased the levels of SOD, GSH and GSH-Px, and alleviated liver injury. Mechanism study showed that dioscin remarkably up-regulated the expression levels of silent information regulator 1 (Sirt1) and heme oxygenase-1 (HO-1) via increasing the nuclear translocation of NF-E2-related factor 2 (Nrf2), and suppressed the expression levels of forkhead box protein O1 (FOXO1) and kelch-like ECH-associated protein-1 (Keap1) to inhibit oxidative stress. Furthermore, disocin obviously decreased the nuclear translocation of nuclear factor κB (NF-κB) and the mRNA levels of tumor necrosis factor (TNF-α), interleukin 1β(IL-1β) and interleukin 6 (IL-6) to suppress inflammation. Meanwhile, disocin significantly regulated tumor suppressor P53 (P53) expression level and BCL2 associated X (BAX)/BCL2 apoptosis regulator (BCL2) ratio to inhibit cell apoptosis. These results were further validated by knockdown of Sirt1 using siRNA silencing in AML12 cells, which confirmed that the target of dioscin against DOX-induced hepatotoxicity was Sirt1/FOXO1/NF-κB signal. In short, our findings showed that dioscin exhibited protective effects against DOX-induced liver damage via suppressing oxidative stress, inflammation and apoptosis, which should be developed as one new candidate for the prevention of DOX-induced liver injury in the future.